2021
DOI: 10.1038/s41467-021-20955-5
|View full text |Cite
|
Sign up to set email alerts
|

An antibonding valence band maximum enables defect-tolerant and stable GeSe photovoltaics

Abstract: In lead–halide perovskites, antibonding states at the valence band maximum (VBM)—the result of Pb 6s-I 5p coupling—enable defect-tolerant properties; however, questions surrounding stability, and a reliance on lead, remain challenges for perovskite solar cells. Here, we report that binary GeSe has a perovskite-like antibonding VBM arising from Ge 4s-Se 4p coupling; and that it exhibits similarly shallow bulk defects combined with high stability. We find that the deep defect density in bulk GeSe is ~1012 cm−3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 41 publications
(59 reference statements)
7
89
2
Order By: Relevance
“…Finally, Ge is in the 2+ oxidation state in both GeS and GeSe and adopts a distorted local structure, which suggests they may have stereochemically active lone pairs. [17][18][19] These properties, along with the recently reported 5.2% power conversion efficiency for a GeSe solar cell 20 , demonstrate the potential of these materials.…”
Section: Ges and Gese Photovoltaicssupporting
confidence: 54%
“…Finally, Ge is in the 2+ oxidation state in both GeS and GeSe and adopts a distorted local structure, which suggests they may have stereochemically active lone pairs. [17][18][19] These properties, along with the recently reported 5.2% power conversion efficiency for a GeSe solar cell 20 , demonstrate the potential of these materials.…”
Section: Ges and Gese Photovoltaicssupporting
confidence: 54%
“…forms by an in-plane vibration along the armchair direction, indicating an intrinsic ferroelectric vibration mode in one layer of bulk GeSe, which agrees with previous experiment work (Zhao et al, 2018). Monolayer GeSe has been predicted a member of ferrovalley materials with plenty of fantastic physical properties (Morales-Ferreiro et al, 2017;Shen et al, 2018;Liu et al, 2021). Thus, it is necessary to investigate the Raman spectrum dependence of fewlayer.…”
Section: Raman Active Modes Of Bulk and Few-layer Gesesupporting
confidence: 85%
“…[ 70 ] Hu's group did a series of studies on GeSe for PV application. [ 37,145–147 ] In particular, combined with theoretical and experimental analysis, they confirmed that the efficiency of PV device previously fabricated by CdS/GeSe heterojunction was predominantly limited by interfacial defects, rather than bulk defects in GeSe (Figure 6g). Then, they focused on the interfacial defect passivation by introducing Sb 2 Se 3 layer between GeSe and CdS, resulting in a record efficiency of 5.2% for GeSe‐based solar cells to date (Figure 6i).…”
Section: Pb‐free Ns2‐cation‐containing Semiconductors For Optoelectronic Applicationssupporting
confidence: 68%
“…Then, they focused on the interfacial defect passivation by introducing Sb 2 Se 3 layer between GeSe and CdS, resulting in a record efficiency of 5.2% for GeSe‐based solar cells to date (Figure 6i). [ 37 ] The device also exhibited excellent humidity and light stability. It was previously reported that a phototransistor fabricated by GeSe nanosheets can achieve a remarkable responsivity of ≈1.6 × 10 5 A W −1 .…”
Section: Pb‐free Ns2‐cation‐containing Semiconductors For Optoelectronic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation